Cardiopulmonary Resuscitation in Children With In-Hospital and Out-of-Hospital Cardiopulmonary Arrest Multicenter Study From Turkey - KUTLU, NURETTİN ONUR; Kendirli, Tanil; Erkek, Nilgun; Koroglu, Tolga; Yildizdas, Dincer; Bayrakci, Benan; Guzel, Ahmet; Citak, Agop; Demirkol, Demet; Agin, Hasan; Arslankoylu, Ali Ertug; Kutlu, NURETTİN ONUR; et al. (My University, 2015)
Objectives The objectives of this study were to determine the causes, location of cardiopulmonary arrest (CPA) in children, and demographics of cardiopulmonary resuscitation (CPR) in Turkish pediatric emergency departments and pediatric intensive care units (PICUs) and to determine survival rates and morbidities for both in-hospital and out-of-hospital CPA.